Regulation of inner nuclear membrane associated protein degradation - Bailey Koch; Hong-Guo Yu (Nucleus, 2019)
The nucleus is enclosed by a double-membrane structure, the nuclear envelope, which separates the nucleoplasm from the cytoplasm. The outer nuclear membrane is continuous with the endoplasmic reticulum (ER), whereas the inner nuclear membrane (INM) is a specialized compartment with a unique proteome. In order to ensure compartmental homeostasis, INM-associated degradation (INMAD) is required for both protein quality control and regulated proteolysis of INM proteins. INMAD shares similarities with ER-associated degradation (ERAD). The mechanism of ERAD is well characterized, whereas the INMAD pathway requires further definition. Here we review the three different branches of INMAD, mediated by their respective E3 ubiquitin ligases: Doa10, Asi1-3, and APC/C. We clarify the distinction between ERAD and INMAD, their substrate recognition signals, and the subsequent processing by their respective degradation machineries. We also discuss the significance of cell-cycle and developmental regulation of protein clearance at the INM, and its relationship to human disease.